The Russian Army and Navy ober-priest G. I. Mansvetov: the Pages ofhistory of the Army and Navy Clergy (19.09.1827-12.11.1832) - Sergey Yuryevich Chimarov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to the activity of G. I. Mansvetov - the fourth in the history of the Russian Armed Forces chief priest of the Army and Navy, who went down in history of military clergy as a theologian, adherent of religious and moral education of soldiers and zealous guardian of military chaplains and their families.